ECOLOGICALASPECTS OF PARASITIC HELMINTHS OF LORNA DRUM SCIAENA DELICIOSA (TSCHUDI, 1846) (PERCIFORMES: SCIAENIDAE) ACQUIRED AT THE FISHING TERMINAL OF VENTANILLA, CALLAO, PERU - Chero, Jhon (2014)
The aim of this study was to assess the ecology of helminth parasites from 35 Sciaena deliciosa of the Terminal of Fish from Ventanilla, Peru during the months of January to May 2013. The parasites were collected and evaluated using standard protocols. The four most prevalent parasites and mean abundance were Cynoscionicola sciaenae (Tantaleán, 1974) (Monogenea); Helicometra fasciata (Rudolphi, 1819) (Trematoda), Dycheline (Cucullanellus) amaruincai (Freitas, Vicente & Ibañez, 1969) (Nematoda) and Corynosoma obtuscens (Lincicome, 1943) (Acanthocephala). Endoparasites predominance on ectoparasites was observed. All five helminths showed with aggregation indices a clumped distribution and only Hargicotyle louisianensis (Hargis, 1955) Mamaev, 1972 (Monogenea) was evenly distributed. The prevalence and abundance of D. amaruincai and Diphyllobothrium pacificum (Nybelin, 1931) (Cestoda) were correlated with the total length of the host. The sex of S. deliciosa was observed to be related to the prevalence and abundance of D. amaruincai. Regarding the relative condition factor (k ) n only fish parasitized by C. sciaenae and ectoparasites had higher values compared with nonparasitized. Infective stages of Anisakis sp, C. obtuscens and D. pacificum were also found with zoonotic importance on the Peruvian coast. The monogeneos H. louisianensis and Macrovalvitrema sp. are considered new records for the Peruvian coast.